News - article Editorial (Union of pediatricians of Russia, 2021)
FDA APPROVED THE MEDICATION FOR SKIN ITCHING ASSOCIATED WITH PROGRESSIVE FAMILIAL INTRAHEPATIC CHOLESTASIS.ADVANCES IN TYPE 2 DIABETES MANAGEMENT IN CHILDREN.FIRST ORAL MEDICATION FOR THE TREATMENT OF CHILDREN WITH MULTIPLE SCLEROSIS WAS APPROVED.THE WORLD'S FIRST MEDICATION FOR THE TREATMENT OF SHORT BOWEL SYNDROME WAS REGISTERED IN RUSSIAN FEDERATION.